2017
DOI: 10.3390/ijerph14111312
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Insecticide Net Ownership, Access and Use in Southwest Ethiopia: A Community-Based Cross-Sectional Study

Abstract: Introduction: A large proportion of the Ethiopian population (approximately 68%) lives in malaria risk areas. Millions of long-lasting insecticide treated nets (LLINs) have been distributed as part of the malaria prevention and control strategy in the country. This study assessed the ownership, access and use of LLNs in the malaria endemic southwest Ethiopia. Methods: A community-based cross-sectional study was conducted in southwest Ethiopia during October–November 2015, including 836 households from sixteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 34 publications
7
33
2
Order By: Relevance
“…In current study independent factors for ITNs use were educational status of respondents, having separated sleeping room, frequency of using ITNs, ITNs ever been washed and shape preference of respondents. Similarly studies done in Wanago, Harari,Kersa and Gilgelgibe in Ethiopia showed that educational status of respondents were predictive factor for LLINs utilization (Tulu et al, 1993;Tomass et al, 2011;FMOH, 2015;Seyoum et al, 2017). The current study showed that literates were 1.88 times more likely to use ITNs than their counter parts.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In current study independent factors for ITNs use were educational status of respondents, having separated sleeping room, frequency of using ITNs, ITNs ever been washed and shape preference of respondents. Similarly studies done in Wanago, Harari,Kersa and Gilgelgibe in Ethiopia showed that educational status of respondents were predictive factor for LLINs utilization (Tulu et al, 1993;Tomass et al, 2011;FMOH, 2015;Seyoum et al, 2017). The current study showed that literates were 1.88 times more likely to use ITNs than their counter parts.…”
Section: Discussionsupporting
confidence: 71%
“…Similarly study done in Wanago literates were 1.31 times more likely to use ITNS than their counter parts (FMOH, 2004). Differently study done in Gilgel Gibe South West Ethiopia Illiterates were 2.3 times more likely not to use ITNs than those who learned grade 9 or above (Seyoum et al, 2017). This is because educated people are more likely to get knowledge through formal learning or by reading any form of readable materials and even more access and understand information from mass media.…”
Section: Discussionmentioning
confidence: 88%
“…to receive an RDT test-it is an opportunity to reinforce health behaviours like net use-this is why it is good to use every opportunity of an encounter with the health service to reinforce positive health behaviours-as sustaining these behaviours is critical for malaria control. The number of household members is another factor influencing use of mosquito nets [29,30]. Women from households with less than 5 members were more likely to use mosquito nets than those whose household members were 5 or more.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in different regions or settings in Ethiopia reported differences in the prevalence of ITN utilization ranging from 37 to 91% [36,37,51]. Access has been a challenge to ITN usage [37][38][39][40][41]. Many studies reported that attitudes predict ITN use [36,49,52,54].…”
Section: Discussionmentioning
confidence: 99%
“…Its effectiveness is much stronger when supported by access to resources (e.g. ITNs) [36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%